Physical activity, physical fitness, sedentary behaviour and screen time profiles of primary school children in a school within the Makana Municipality, Eastern Cape, South Africa - Kade, Andréa Gaby (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
There is a lack of data on the physical activity, physical fitness and sedentary behaviour of children in South Africa. Furthermore chronic diseases such as type II diabetes and coronary heart disease have been linked to childhood inactivity, and improving cardiorespiratory fitness and increasing levels of physical activity has been shown to be beneficial in reducing the risk of such diseases. In South Africa more broadly there is a lack of information on levels of physical activity and sedentary behaviour as well as physical fitness measures particularly in children. Objective: The purpose of this study was to enhance the existing body of knowledge on this, by measuring the prevalence of physical inactivity, sedentary behaviour and screen time of primary school children in a private school from the Makana Municipal region in the Eastern Cape Province of South Africa, where the evidence is most sparse. A secondary aim was to assess levels of physical fitness in this cohort, as well as to compare across grades and sexes. Method: After ethical approval was granted, stature and body mass measurements were taken and body mass index was computed for primary school children (Grade one to seven) from a private school in the Makana Municipality. Sitting stature was measured in order to determine each child's peak height velocity and maturity offset. Five different physical fitness tests were conducted on the children and blood pressure and heart rate values were measured at rest. Physical activity and screen time questionnaires were completed by the children's parents for a seven day period. Results: Females were found to mature faster than males. In addition females were more physically active (Females= 916 min/week; Males= 669 min/week) while also accumulating more sedentary time (Females= 1241 min/week; Males= 970 min/week) as compared to males, although no significant differences were found between males and females for these variables. The sample participated in more than 60 minutes of moderate-to-vigorous physical activity and less than two hours of screen time daily, which is in accordance with guidelines. No differences were found between grades and sexes for accumulated screen time. Strength increased significantly with grade and age, and there were also statistical differences between the sexes for all three strength measures with males being stronger than females. Females were more flexible than males and no statistical differences were found between sexes for the shuttle run test. Blood pressure correlated positively with mass, as did all the strength measures as well as maturity offset. No correlations were found between screen time and all other variables. A negative relationship was recorded between screen time and physical activity, although not significant. For females a strong positive correlation was found between sedentary behaviour and physical activity. Conclusion: The study was successful in adding to the body of knowledge regarding the prevalence of physical inactivity, sedentary behaviour and screen time within school children from the Makana Municipality in the Eastern Cape Province of South Africa. The sample was considered physically active as they accumulated on average more than 60 minutes of moderate-to-vigorous physical activity daily (Males= 96 min/day; Females 130 min/day), which is in accordance with guidelines recommended by the World Health Organization (World Health Organization, 2018). The sample accumulated more sedentary behaviour than physical activity, although not significant. Screen time was below regulations of two hours daily, indicating this population participated in more non screen related sedentary behaviour. More research is needed into the risks presented with different forms of sedentary behaviour. Physical fitness increased with increasing grade and age and males were considerably more fit. The current study did not present any concern with regards to the effects of increased physical activity and fitness levels within school aged children. More research into the current levels of physical activity, physical fitness and sedentary behaviour of school aged children in South Africa in general, and in the Eastern Cape Province, is needed.
Keywords: Sedentary behavior in children -- South Africa -- Makana Municipality; Physical fitness for children -- South Africa -- Makana Municipality; Exercise -- Physiological aspects; Exercise -- Health aspects; Diabetes -- Risk factors; Heart -- Diseases -- Risk factors